STRATEGI ADAPTASI EKOLOGIS DAN PENGENTASAN KEMISKINAN PADA MASYARAKAT SEKITAR TAMAN NASIONAL GUNUNG HALIMUN SALAK - rita rahmawati (Jurnal Sosial Humaniora, 2011)
Long term goal of this study is to improve the welfare of people around Gunung Halimun Salak National Park forest which is located in Kabupaten Bogor and Lebak trough advocation of academic draft for poverty eradication policy for local government, the implementation of ecological adapation model, and new alternative income strategic. The study result in time hopefully could be published in national accreditated journal. The specific target of the study is developing ecological adaption model and new income strategic which is pro to human welfare and natural conservation; and academic draft of policy strategy for poverty eradication. Ecological adaption and new income strategic refers to the data of forest ecology social institution system wether original or adaption result with various knowledge exercises and government (institution) policy; how the exist institution could survive and also could guarantee the livelihood sustainable of the people, or vise versa. The necessary data is gathered from literature study and in-depth interview, focus group discussion and seminar. Actual data comes from household around the forest which is categorized based on royal customary society (masyarakat adat kasepuhan) and common people. In the first year, designing ecological adaptation model and new income strategic which is tend to human welfare and natural conservation. Model that formulated in the first year will be implemented in the second year with action research method approach wich will be evaluated in the end of the year. Evaluation result will be formulated in academic draft of poversty eradication strategic policy which considering